Ceramide-Induced Cell Death Depends on Calcium and Caspase-Like Activity in Rice - Zhang, Quan-Fang; Li, Jian; Bi, Fang-Cheng; Liu, Zhe; Chang, Zhen-Yi; Wang, Ling-Yan; Huang, Li-Qun; Yao, Nan (Frontiers in Plant Science, 2020)
Ceramide sphingolipids are major components of membranes. C2 and C6 ceramides induce programmed cell death (PCD) in animals and plants, and we previously showed that C2 and C6 ceramides induce PCD in rice (Oryza sativa) protoplasts. However, the mechanistic link between sphingolipids and PCD in rice remains unclear. Here, we observed that calcium levels increased rapidly after ceramide treatment. Moreover, the calcium channel inhibitor LaCl3 and the intracellular calcium chelator acetoxymethyl-1, 2-bis (2-aminophenoxy) ethic acid (BAPTA-AM) inhibited this calcium increase and prevented ceramide-induced PCD. Moreover, caspase-3-like protease activity increased significantly in C6 ceramide-treated protoplasts, and a caspase-specific inhibitor prevented C6 ceramide-induced cell death. We also detected the other typical PCD events including ATP loss. DIDS (4, 49-diisothiocyanatostilbene- 2, 29-disulfonic acid), an inhibitor of voltage-dependent anion channels (VDACs), decreased C6 ceramide-induced cell death. Together, this evidence suggests that mitochondria played an important role in C6 ceramide-induced PCD.